A exortação da guerra - o ideal da cruzada aos infiéis e as conquistas marítimas portuguesas - Lenora Pinto Mendes (Navigator)
In the late fifteenth century Portugal turned their eyes to the sea and became the first European nation to dominate the “ocean.” The Portuguese seafarers’ feat during the sixteenth century opens up a world hitherto unknown to Europeans. The conquest of new lands and the trade with the East brought to the Portuguese kingdom endless riches beyond the exotic eastern world that can be observed through the chronicles, in the garments and parties organized by the court and in architecture through the Manueline. The Portuguese court theater, with its leading playwright - Gil Vicente, will colaborate with this process working as propaganda for the exaltation of the king and kingdom and the feat of the Portuguese overseas. Paradoxically, the official discourse that permeates this whole process is that of the medieval ideal of the crusade to convert the infidels to Christianity.